Utilization Of Geolocation-Based Authentication on Online Exams - Wibisono, Muhammad Nurwiseso; Anggriani, Swastika Dhesti (Universitas Negeri Malang, 2024)
In the industrial era 4.0, technology is utilised as much as possible to advance the welfare of life. One use of technology commonly used in education is online-based exams. In addition to saving paper, online-based exams can reduce operational costs in carrying out exams. Currently, many online-based exam models are used for various types of exams. Starting with the computer-based Test, CAT-based CPNS test, etc., researchers developed a method by utilising geolocation to run an online-based examination system. In this study, the author wants to utilise geolocation as one of the requirements for accessing needed resources; in this case, the online-based quiz system was adopted. Using geolocation in the online-based quiz system is expected to provide security for the examination system so that examiners can assess their students as best they can